Smoothing Methods for Continuous Permeation Data Measured Discretely Designated for Quick Evaluation of Barrier Materials (Advances in Military Technology, 2023)
Information concerning barrier properties of materials used for production of personalprotective equipment fundamentally not only affects their useful properties, but alsosupports the end users’ decisions. Data obtained from measurements by standardizedmethods have to be processed by appropriate statistical methods. The article deals withnumerical and statistical methods of reconstruction of a continuous curve out of discretely measured data. These mathematical models are proposed as an extension to the manual measurement of a conductometric method. Behaviour of these models is demonstrated on two chemical warfare agent simulants, however, the proposed methodology is universal and can be applied also to chemicals which have no conductivity. The parametric and nonparametric models are studied in the curve reconstruction, as well as in the calculation of subsequent characteristics, for example, a lag-time. The nonparametric model shows the best results which are in accordance with an expert’s estimate.
Keywords: hazardous chemicals; permeation; concentration; nonparametric; regression; derivative